Human Rights in the Remnants of a Conflict: Has the Legacy of Dayton Impaired Minority Inclusion in Bosnia-Herzegovina? - Michilli, Adriana (Political Preferences, 2019)
More than two decades following the end of civil conflict made possible via Dayton Peace Accords (DPA) instated in 1995, Bosnia-Herzegovina still utilizes this international legal instrument as the sovereign’s official constitution. This paper addresses the impact that the international community’s failure to implement the appropriate locally considerate solutions needed to sustain peacebuilding has left behind. To this end, the paper highlights the quotidian ways in which the socio-cultural landscape of the Bosnian Federation and Republika Srpska remain stratified along ethno-religious divisions. Directing its’ attention on the practical aspects where minorities face discrimination and remain excluded from social spheres the paper calls for a necessary advancement on the human rights protection of safeguarding minority members in both of the country’s de-facto territories. In closing, it argues that society’s schism from the residual consequences of the DPA can be achieved through the practices of change-drivers taking advantage of their training and capacity-building skills in the forms of: inter-ethnic dialogue, inter-cultural reconciliation and inter-religious peace. Constructing competences which demonstrate respect for human rights, encourage co-existence and the equal integration of minority members in society also bear the potential to strengthen the currently fragile relations with the out-group community, reducing a society’s propensity for conflict regression.